Forward vs Backwards Counting Effects on Time Estimation Under Retrospective and Prospective Paradigms - Vashisht, Shaurya (Thapar Institute of Engineering and Technology, 2025)
This study explores the impact of counting direction on time perception in both retrospective and prospective paradigms. Two experiments were conducted to examine how counting direction (backwards vs. forward) influences subjective time estimation, while also controlling for working memory capacity using the Letter-Number Sequencing (LNS) task from the WAIS-III. Experiment 1 used a between-subjects design involving 100 participants (N=100) to examine retrospective time estimation. Participants were not informed that they would need to judge time until after they completed the task. The results showed significant differences between the conditions: participants who counted backwards overestimated the duration, estimating an average of 8.320 seconds (± 2.714), while those who counted forwards slightly underestimated the interval, with an average estimate of 6.280 seconds (± 2.711) for a fixed 7-second duration. In Experiment 2, we conducted a within-subjects design with 50 participants to investigate prospective time estimation, where participants were informed beforehand that their time judgments would be relevant. The results showed similar patterns: backwards counting resulted in an overestimation of time, with an average of 7.620 seconds (± 1.615 seconds), while forward counting led to a slight underestimation, averaging 6.880 seconds (± 1.531 seconds). In both conditions, participants counted significantly fewer numbers in the backwards task than in the forward task, indicating that the backwards condition imposed a higher cognitive load. No significant differences were found in the LNS scores between the two conditions, which confirms that working memory capacity did not affect the results. These findings support established theoretical frameworks, including Ornstein's storage-size hypothesis and Block and Reed's contextual-change hypothesis for retrospective timing, while challenging traditional 15 interpretations of the Attentional Gate Model for prospective timing. The study demonstrates that the direction of the task significantly influences time perception by creating different cognitive demands. This has important implications for clinical, educational, and experimental contexts. Keywords: time perception; retrospective time estimation; prospective time estimation; counting direction; working memory; cognitive load; attentional gate model; contextual change hypothesis; storage-size hypothesis
Keywords: Time Perception; Temporal processing; Retrospective Time Estimation; Prospective Time Estimation; Counting Direction; Working Memory